2023
DOI: 10.1080/21505594.2023.2190650
|View full text |Cite
|
Sign up to set email alerts
|

An important call: Suggestion of using IL-10 as therapeutic agent for COVID-19 with ARDS and other complications

Abstract: The global coronavirus disease 2019 (COVID-19) pandemic has a detrimental impact on public health. COVID-19 usually manifests as pneumonia, which can progress into acute respiratory distress syndrome (ARDS) related to uncontrolled TH17 immune reaction. Currently, there is no effective therapeutic agent to manage COVID-19 with complications. The currently available anti-viral drug remdesivir has an effectiveness of 30% in SARS-CoV-2–induced severe complications. Thus, there is a need to identify effective agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 153 publications
0
11
0
Order By: Relevance
“…Strikingly, our results showed that cells corresponding to the FA100 group synthetized and secreted the lowest amounts of immune system signaling molecules, with a significant reduction of all the analyzed molecules except IL10. Due to the fact that IL10 is known to exert potent anti-inflammatory effects ( Shih et al, 2023 ), whereas most of the other molecules analyzed here are strong pro-inflammatory factors ( Niedźwiedź et al, 2022 ), our results could imply that FIBRIAGAR-3D is not associated to an increase in the inflammatory potential of cells cultured in this system. The reduced presence of these signaling molecules in the FA100 group could be related to the capability of FIBRIAGAR-3D to reproduce the microenvironment of the native tissues more efficiently than traditional 2D culture systems.…”
Section: Discussionmentioning
confidence: 71%
“…Strikingly, our results showed that cells corresponding to the FA100 group synthetized and secreted the lowest amounts of immune system signaling molecules, with a significant reduction of all the analyzed molecules except IL10. Due to the fact that IL10 is known to exert potent anti-inflammatory effects ( Shih et al, 2023 ), whereas most of the other molecules analyzed here are strong pro-inflammatory factors ( Niedźwiedź et al, 2022 ), our results could imply that FIBRIAGAR-3D is not associated to an increase in the inflammatory potential of cells cultured in this system. The reduced presence of these signaling molecules in the FA100 group could be related to the capability of FIBRIAGAR-3D to reproduce the microenvironment of the native tissues more efficiently than traditional 2D culture systems.…”
Section: Discussionmentioning
confidence: 71%
“…4b). The z score was also higher for IL-10, with IL-10 elevated in severe COVID-19, but also able to suppress hyper-cyotokinemia [1820]. Elevated IL-4, IL-9 and IL-13 have been associated with more severe disease [21, 22, 91], although IL-9, IL-13 (and IL-5) are produced by type 2 innate lymphoid cells (ILC2 cells) [92] (see below), and increased IL-4 and IL-13 signatures may (in this context) reflect a relatively more balanced Th1/Th2 response [25, 26].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated mRNA or protein levels of a range of cytokines have been identified in peripheral blood of severe COVID-19 patients, these include inter alia IL-6, IL-1, IL-2, IL-17, IL-18, TNF, IFNG and CSF2 (GM-CSF) ( ibid ). Elevated IL-10 in the peripheral blood has also been associated with severe disease, but may be useful later in the infection to suppress the hyper-cytokinemia associated with ARDS [1820]. Elevated Th2 [10, 2123] and Th17 responses [10, 24] have been associated with poor outcomes, with Th1/Th2 [2527] and Th1/Th17 imbalances [28] also reported to be detrimental.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple aberrant pathways interconnect to result in pulmonary fibrosis in a subset of individuals who develop ARDS 44 . Important mediators include the dysregulated release of matrix metalloproteinases during the inflammatory phase of ARDS, which causes epithelial and endothelial injury and unchecked fibroproliferation 45 (Figure 4 A,B). Canonical profibrotic pathways regulated by TGF‐β are important, and there is evidence that vascular dysfunction is a key component of the switch from ARDS to fibrosis, with VEGF and cytokines such as interleukin 6 (IL‐6) and TNF‐α implicated 46,47 .…”
Section: Roles Of Tcs Mediated Cell Communication In Pulmonary Fibros...mentioning
confidence: 99%